Common Good HRM: A paradigm shift in Sustainable HRM? - Aust, Ina; Matthews, Brian; Muller-Camen, Michael (Human resource management review, 2020)
As organizations increasingly claim to have become more sustainable and to have contributed to global sustainable development, demands for Human Resource Management (HRM) to become sustainable intensify. In the past decade, the concept of Sustainable HRM received increasing attention in both practice and research. However, academics' views about what Sustainable HRM means are diverse, and the effectiveness of Sustainable HRM practices is uncertain. We reviewed key articles in the literature on Sustainable HRM and as a result highlight how the purpose of HRM has been transformed in the search for sustainability. We present four Sustainable HRM types and describe how HRM can effectively contribute to solving todays “grand” sustainability challenges by applying ideas from a common good economy perspective. We propose that a new type of Sustainable HRM – Common Good HRM – could be essential in driving progress toward addressing sustainable development goals (SDGs) in Sustainable HRM. •A classification of research on Sustainable HRM•The potential of Common Good HRM to become a new paradigm in Sustainable HRM•Provision of examples for Common Good HRM